2003
DOI: 10.1109/tasc.2003.812380
|View full text |Cite
|
Sign up to set email alerts
|

Twin spacing and its correlation with critical current density in melt-textured YBCO with yttria nanoparticle addition

Abstract: Twin boundaries have been proved to be effective flux pinning centers in YBa 2 Cu 3 O 7 (YBCO). Increases in twin density yield higher values of critical current density. Twin spacings in melt-textured grown (MTG) YBCO with different amounts of yttria nanoparticles were investigated with a new x-ray method. Twin spacings from the x-ray method were compared with those from transmission electron microscopy to show applicability. From investigation, MTG-YBCO with 11.9 weight percent yttria and oxygenation tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…S fr determines the stability of twin microstructure and gives possibility to estimate natural limit of its reduction (see for details [34]). The theoretical consideration and experimental investigations show validity of proposed methods of determination of the twin boundary energy and S fr [34,35,39,40]. After determination of numerical values of phenomenological parameters in YBCO, one can use the dislocation thin twin theory to the full extent.…”
Section: Determination Of the Phenomenological Parameters Of The Thinmentioning
confidence: 83%
See 1 more Smart Citation
“…S fr determines the stability of twin microstructure and gives possibility to estimate natural limit of its reduction (see for details [34]). The theoretical consideration and experimental investigations show validity of proposed methods of determination of the twin boundary energy and S fr [34,35,39,40]. After determination of numerical values of phenomenological parameters in YBCO, one can use the dislocation thin twin theory to the full extent.…”
Section: Determination Of the Phenomenological Parameters Of The Thinmentioning
confidence: 83%
“…The possibility was found to govern twin microstructure large grain YBCO without changing the grain size by incorporating in YBCO matrix the large volume fractions of dispersed addition of (211) in the form of small particles [30,31], dopants [34], and additives such as yttrium nanoparticles [40]. In those cases, the samples were heavily twinned and demonstrate better superconductive properties.…”
Section: Formation Of a Twin In The Presence Of An Embedded Particlementioning
confidence: 99%
“…Hoping to improve superconductive properties of polycrystal YBCO we can make twin microstructure finer by decreasing grain size, but this increases total area of GBs and drops J c . A method was found to control twin microstructure large grain YBCO without changing the grain size by incorporating in the YBCO matrix large well-dispersed volume fractions of dispersed addition of Y 2 BaCuO 3 (2 1 1) in the form of small particles [15], dopants [16], and additives such as yttrium nanoparticles [18]. In those cases, the samples were heavily twinned and demonstrate better superconductive properties.…”
Section: Theoretical Considerationmentioning
confidence: 99%
“…This force determines the stability of twin microstructure and allows for an estimation of the natural limit of its reduction. The theoretical considerations and experimental investigations demonstrate the validity of the proposed methods [16,[18][19][20]. In this article, we try to estimate the resources of twin microstructure design in YBCO by twinning for enhanced J c at high magnetic fields.…”
Section: Introductionmentioning
confidence: 97%
“…16,17,19,20 Recently, it has become possible to fabricate high-density TBs in melt grown YBCO, and the pinning enhancement has been reported in the fabricated samples. [26][27][28] However, vortex dynamics in superconductors with high-density TBs are not clear. Although several numerical studies about the dynamics of vortices interacting with TBs have already been reported, the twin spacing T w is much larger than the vortex spacing d in these studies.…”
Section: Introductionmentioning
confidence: 99%